Improved discus technique but no extra distance, is rhythm your problem? (Coaching Track & Field Athletics)
Technique and rhythm would never not be seen as important by any discus coach. However in many cases these two aspects are often neglected in the development of discus technique, especially throwing rhythm. But the fact is that what often is the problem is not a change in technique but a change or lack of rhythm.